HOXC10 promotes proliferation and invasion and induces immunosuppressive gene expression in glioma. (25th May 2018) - Li, Shu; Zhang, Wenhao; Wu, Chao; Gao, Hongliang; Yu, Jun; Wang, Xiaoqiang; Li, Bin; Jun, Zhong; Zhang, Wenchaun; Zhou, Ping; Shi, Juanhong; Wang, Lifeng; et al.
Abstract : The prognosis for patients with malignant glioma is very poor and thus the identification of new potential therapeutic targets is critically important. In this work, we report a previously unknown role for the homeobox transcription factor HOXC10 in regulating immunosuppressive gene expression in glioma cell lines and their proliferative and invasive capacities. Although HOXC10 expression is dysregulated in several types of tumors, its potential function in glioma was not known. We found that HOXC10 expression was upregulated in glioma compared with normal tissue, and that HOXC10 expression positively associated with high grading of glioma. In three independent datasets (REMBRANDT glioma, The Cancer Genome Atlas glioblastoma multiforme and GSE4412), HOXC10 upregulation was associated with short overall survival. In two glioma cell lines, HOXC10 knock‐down inhibited cell proliferation, colony formation, migration and invasion, and promoted apoptosis. In addition, HOXC10 knock‐down suppressed the expression of genes that are involved in tumor immunosuppression, including those for transforming growth factor‐β 2, PD‐L2, CCL2 and TDO2. A ChIP assay showed that HOXC10 directly bound to the PD‐L2 and TDO2 promoter regions. In summary, our results suggest that HOXC10 upregulation in glioma promotes an aggressive phenotype and induces immunosuppressive gene expression, supporting further investigation of the potential of HOXC10 as a therapeutic target in glioma. Abstract : The function of the homeobox transcription factor HOXC10 in regulating aggressive phenotypes and immunosuppressive gene expression in glioma is reported. HOXC10 expression was upregulated in glioma compared with normal tissue, and positively associated with high grading of glioma. HOXC10 up regulation was associated with short overall survival. In two glioma cell lines, HOXC10 knock‐down inhibited aggressive phenotypes and suppressed the expression of transforming growth factor‐β 2, PD‐L2, chemokine (C–C motif) ligand 2 and tryptophan 2, 3‐dioxygenase.